Potential of Bituminous Coal to Become Nanocarbon Using the Hydrothermal Method - Muhammad Abdul Halim; Indra Surya (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This research investigates the potential of bituminous coal from Sawahlunto, Indonesia, as a raw material for nanocarbon synthesis using a hydrothermal method. The study aims to enhance the economic value of coal by exploring its transformation into nanocarbon. The process involves stages of preparation, carbonization, and hydrothermal at varying temperatures (120°C, 150°C, and 180°C) durations (2 and 4 hours). Fourier Transform Infrared (FT-IR) spectroscopy, X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM) were employed to characterize the resulting nanocarbon. The hydrothermal process improved the crystallinity of coal from 51% to 57% and reduced its particle size to 47.71 nm. SEM and TEM analyses revealed a more uniform and refined morphology in the nanocarbon compared to raw coal. The study underscores the effectiveness of the hydrothermal method in optimizing the physical and structural properties of coal-derived nanocarbon, paving the way for its potential application in various industries.